Local communities' perceptions towards economic impact of rural tourism development in Kilim Geopark, Langkawi - Ahmad, Nurul Azwa; Shuib, Ahmad (Faculty of Economics and Business, UNIMAS, 2012)
Purpose – The study identifies the local communities’ perception on economic impacts in a rural area whom experiencing an economic transition. The studies focus on residents in the area of popular tourism developments in the region. Design/Methodology/Approach – Likert scale will be use to measure perceptions on economic impacts, question will be asked about indicators in economic impacts that happening in that area, the questionnaire involve their perceptions will be positive or negative impacts and whether they are agree or disagree with tourism development that happening in that area. Results/Originality – The finding from these studies will emphasizes the importance of perceptions of local communities’ as criteria to determine the effectiveness of rural tourism development in Kilim Geopark, Langkawi, local communities’ perception is also importance to guide tourism development in that area and these studies also could be beneficial to provide information to the government and also Langkawi Development Authority (LADA) in term of making appropriate decisions for future development of the rural tourism development sector. Finally, from all economic indicators that have been measured, one numerical indicator of impacts of rural tourism development will come out from the finding of the results.